Microencapsulating Alginate-Based Polymers for Probiotics Delivery Systems and Their Application - Xiaochen Wang; Shukun Gao; Shuaiting Yun; Mingjing Zhang; Liyang Peng; Yingxiu Li; Yanxia Zhou (MDPI AG, 2022)
Probiotics exhibit many health benefits and a great potential for broad applications in pharmaceutical fields, such as prevention and treatment of gastrointestinal tract diseases (irritable bowel syndrome), prevention and therapy of allergies, certain anticancer effects, and immunomodulation. However, their applications are limited by the low viability and metabolic activity of the probiotics during processing, storage, and delivery in the digestive tract. To overcome the mentioned limitations, probiotic delivery systems have attracted much attention. This review focuses on alginate as a preferred polymer and presents recent advances in alginate-based polymers for probiotic delivery systems. We highlight several alginate-based delivery systems containing various types of probiotics and the physical and chemical modifications with chitosan, cellulose, starch, protein, fish gel, and many other materials to enhance their performance, of which the viability and protective mechanisms are discussed. Withal, various challenges in alginate-based polymers for probiotics delivery systems are traced out, and future directions, specifically on the use of nanomaterials as well as prebiotics, are delineated to further facilitate subsequent researchers in selecting more favorable materials and technology for probiotic delivery.